Hubungan Faktor Kesadaran, Kemampuan Dan Keterampilan Perawat Dengan Kualitas Pelayanan Perawatan Anak Di Rumah Sakit Umum Muhammadiyah Babat Lamongan - Oktavia, Nafakha; Kusbiantoro, Dadang; Harmiardillah, Sylvi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
The quality of healthcare services significantly affects patient satisfaction and care effectiveness, especially in pediatric nursing. Quality nursing care depends on nurses' awareness, abilities, and skills in performing their duties. This study analyzes the relationship between nurses' awareness, abilities, and skills with the quality of pediatric nursing services at Muhammadiyah Babat General Hospital. This research employs a correlational analytic design with a cross-sectional approach. The sample consists of nurses working in pediatric care units, selected using a total sampling technique. Data were collected through a structured questionnaire tested for validity and reliability. Data analysis was conducted using Spearman’s Rho test to determine the relationship between the independent variables (awareness, abilities, skills) and the dependent variable (quality of pediatric nursing services). The results indicate a significant relationship between nurses' awareness and the quality of pediatric nursing services (p < 0.05). Additionally, nurses' abilities and skills also show a significant correlation with care quality. Awareness helps nurses understand patients' needs, while their abilities and skills determine the effectiveness of nursing interventions. In conclusion, improving nurses' awareness, abilities, and skills can enhance the quality of pediatric nursing care. Therefore, continuous training and competency development programs are essential to ensure optimal nursing services.